Relação universidade-empresa: um estudo no setor de T.I. do Estado do Rio Grande do Sul - Zanluchi, João Batista (Universidade do Vale do Rio do Sinos, 2008)
The University-Industry relationship is a subject of constant debate in the national sphere. Many studies seek evaluate this relationship in various ways and focus of research. The theoretical reference on the subject shows a lack of studies with a focus on the company. Based on this premise this study investigated the University-Industry relationship in the I.T. sector of the State of Rio Grande do Sul with the objective that evaluate how is the relationship Between companies and universities. The methodology used a two-step method. The firt – exploratory – adopted a qualitative approach, through case study of a company that cooperates with universities and a company that does not establish this kind of relationship. The second one – descriptive – adopted a quantitative approach, based on data collected in a survey where 195 companies formed the sample of search. The data’s analysis found that companies seek to establish projects in partnerships with universities with the main objective of developing capabil
Keywords: aprendizagem; cooperação; inovação; performance; relação universidade-empresa; cooperation; inovation; learning; performance; university-industry relationship; Ciências Sociais Aplicadas